The Effect of Sense of Community and Self-Efficacy on Students' Higher-Order Thinking Skills In WhatsApp-assisted Physics Learning - Ratna Widyaning Tyas; Nengah Maharta; Wayan Suana (Jurnal Pembelajaran Fisika, 2020)
This study aimed to determine the effect of sense of community (SC) on higher-order thinking skills (HOTS), self-efficacy (SE) on higher-order thinking skills (HOTS), and SC and SE on HOTS of students in learning Newton's Law of motion assisted with WhatsApp application. The sample in this research were students of class X MIPA 5 and class XI MIPA 6 with 68 students in total at SMAN 13 Bandar Lampung in the academic year 2019/2020. The research design applied in this study was a one-shot case study. Data analysis techniques using product-moment correlation, simple linear regression, and multiple linear regression. The results showed that there is no effect between SC on HOTS, SE on HOTS, and the effect of the combination of SC and SE on HOTS. With a correlation value 0.095, the coefficient of determination R square of 0.009 and sig 0.441> 0.05, SE on HOTS with a correlation value of 0.052, the determination coefficient of R square of 0.003 and sig of 0.674> 0.05, and combination of SC and SE on HOTS with a correlation value of 0.114, the coefficient of determination R square of 0.013 and sig 0.653> 0.05. Based on the findings, it can be concluded that there is no effect of SC on HOTS, SE on HOTS, and effect of the combination of SC and SE on HOTS in learning physics assisted with WhatsApp application.Keywords: Higher Order Thinking Skills (HOTS), Self-Efficacy (SE), Sense of Community (SC), Whatsapp Application.DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202004